Real Exchange Rates, Structural Reforms and Monetary Union - Carsten Hefeker (Kredit und Kapital, 2009)
Real Exchange Rates, Structural Reforms and Monetary Union The paper addresses the question what effects the enlargement of a monetary union will have on necessary structural reforms in member countries with high and low degrees of distortions. I show that monetary union has asymmetric effects on reform efforts and under what circumstances governments increase their reform efforts. Depending on asymmetries in the degrees of distortions, the stance of monetary policy, and countries' openness, one could expect convergence or divergence in reform efforts. (JEL E61, E63, F33) – – Reale Wechselkurse, Strukturreformen und Währungsunion Der Aufsatz untersucht die Frage, welche Konsequenzen die Erweiterung der Währungsunion haben wird auf die notwendigen Strukturreformen in Ländern mit größeren oder geringeren Verzerrungen. Er zeigt, dass die Währungsunion unterschiedliche Auswirkungen auf die Reformbemühungen haben wird und unter welchen Umständen Regierungen ihre Bemühungen erhöhen werden. Abhängig von den Unterschieden im Ausmaß der Verzerrungen, der Ausrichtung der Geldpolitik und der Offenheit der betroffenen Länder kann man eine Konvergenz oder Divergenz in den Reformbemühungen erwarten.
Keywords: E61; E63; F33; 330